2013
DOI: 10.1007/s00586-013-2920-4
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval analysis of PEEK rods for posterior fusion and motion preservation

Abstract: This study documents the surface changes and tissue reactions for retrieved PEEK rod stabilization systems. Permanent indentations by the set screws and pedicle screws were the most prevalent observations on the surface of explanted PEEK rods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…In some cases, there was an emerging difficulty to distinguish between wear-induced and iatrogenic damages due to revision surgery, as already reported by Kurtz et al [33]. The reduced average roughness in worn areas found in this study has been already documented for a retrieved CFR-PEEK acetabular liner adjacent to an alumina head [34] and for CFR-PEEK acetabular cups tested within a simulator study [17].…”
Section: Discussionsupporting
confidence: 72%
“…In some cases, there was an emerging difficulty to distinguish between wear-induced and iatrogenic damages due to revision surgery, as already reported by Kurtz et al [33]. The reduced average roughness in worn areas found in this study has been already documented for a retrieved CFR-PEEK acetabular liner adjacent to an alumina head [34] and for CFR-PEEK acetabular cups tested within a simulator study [17].…”
Section: Discussionsupporting
confidence: 72%
“…One of them is polyetheretherketone, whose application is becoming greater and greater. [2] To improve PEEK's biocompatibility, the surface was enriched with hydroxyapatite (HA) during polymerization process. Besides, based on past studies, PEEK is well tolerated by the nervous tissue and thus it can be used as a component in the spinal implant.…”
Section: Introduction 1| Peek Application As Implantsmentioning
confidence: 99%
“…Patient age ranged from 35 to 64 years (mean 6 SD: 52 6 10 years); 8 patients (66.7%, 8/12) were female, and the implantation time of the PEEK rods ranged from 0.5 to 2.8 years (mean 6 SD: 1.7 6 0.8 years). 21 All the patients in this study were revised for intractable pain, although the mechanism varied and was confirmed by intraoperative findings. The most frequently reported reasons (58.0%, 7/12) for revision among the PEEK rod patients who underwent spinal fusion included adjacent segment disease in 3 patients, device-related muscular paravertebral pain in 2 patients, and pseudoarthrosis in 2 patients.…”
Section: Peek (N) Fusion Rate (%) Notesmentioning
confidence: 76%
“…19 These data are in alignment with the functional improvement outcomes. 21 Twelve patients with PEEK rods underwent revision surgery, and their posterior instrumentation was retrieved. Patient age ranged from 35 to 64 years (mean 6 SD: 52 6 10 years); 8 patients (66.7%, 8/12) were female, and the implantation time of the PEEK rods ranged from 0.5 to 2.8 years (mean 6 SD: 1.7 6 0.8 years).…”
Section: Peek (N) Fusion Rate (%) Notesmentioning
confidence: 99%
See 1 more Smart Citation